The shift from lament to praise in the psalms: A psychodynamic phenomenon - Strawn, Brent A. (Journal for the study of the Old Testament, 2024)
This article returns to the long-standing problem of the so-called ‘sudden shift of mood’ in the lament psalms, revisiting this shift from petition to praise from the perspective of contemporary psychoanalytic depth psychology, especially via insights offered by object relations psychology. In this light, the movement from lament to praise may be seen as a psychodynamic phenomenon related to, and witnessed in, the therapeutic processes of illumination, subtraction, and addition. This understanding of how the lament psalms work underscores how crucial the expression of mourning is to psychological health. To borrow terms from Walter Brueggemann, the psychological interpretation offered here demonstrates once again ‘the costly loss of lament’, but the high price in question extends beyond that identified by Brueggemann insofar as the subtractive therapeutic action at work in the grieving process is precisely what facilitates the restoration of psychological well-being.